Mean Diffusional Kurtosis in Patients with Glioma: Initial Results with a Fast Imaging Method in a Clinical Setting - Tietze, A. (AJNR Am J Neuroradiol, 2015)
BACKGROUND AND PURPOSE: Diffusional kurtosis imaging is an MR imaging technique that provides microstructural information in biologic systems. Its application in clinical studies, however, is hampered by long acquisition and postprocessing times. We evaluated a new and fast (2 minutes 46 seconds) diffusional kurtosis imaging method with regard to glioma grading, compared it with conventional diffusional kurtosis imaging, and compared the diagnostic accuracy of fast mean kurtosis (MK′) to that of the widely used mean diffusivity. MATERIALS AND METHODS: MK′ and mean diffusivity were measured in the contrast-enhancing tumor core, the perifocal hyperintensity (indicated on T2 FLAIR images), and the contralateral normal-appearing white and gray matter of 34 patients (22 with high-grade and 12 with low-grade gliomas). MK′ and mean diffusivity in the different tumor grades were compared by using a Wilcoxon rank sum test. Receiver operating characteristic curves and the areas under the curve were calculated to determine the diagnostic accuracy of MK′ and mean diffusivity. RESULTS: MK′ in the tumor core, but not mean diffusivity, differentiated high-grade from low-grade gliomas, and MK′ differentiated glioblastomas from the remaining gliomas with high accuracy (area under the curve(MK′) = 0.842; P(MK′) < .001). MK′ and mean diffusivity identified glioblastomas in the group of high-grade gliomas with similar significance and accuracy (area under the curve(MK′) = 0.886; area under the curve(mean diffusivity) = 0.876; P(MK′) = .003; P(mean diffusivity) = .004). The mean MK′ in all tissue types was comparable to that obtained by conventional diffusional kurtosis imaging. CONCLUSIONS: The diffusional kurtosis imaging approach used here is considerably faster than conventional diffusional kurtosis imaging methods but yields comparable results. It can be accommodated in clinical protocols and enables exploration of the role of MK′ as a biomarker in determining glioma subtypes or response evaluation.